2002
DOI: 10.3168/jds.s0022-0302(02)74430-5
|View full text |Cite
|
Sign up to set email alerts
|

The Proportion of the Diet to which Fibrolytic Enzymes are Added Affects Nutrient Digestion by Lactating Dairy Cows

Abstract: Eight lactating Holstein cows, four with ruminal cannulas, were used in a duplicated 4 x 4 Latin square design to investigate a fibrolytic enzyme product characterized by xylanase and cellulase activities (Promote N.E.T. Agribrands International, St. Louis, MO). The diet consisted of concentrate containing rolled barley and supplement, barley silage and alfalfa haylage (55% to 45% DM basis, forage to concentrate ratio) and differed in enzyme application: 1) control, 2) enzyme applied to concentrate (45% of TMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
0
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 23 publications
11
66
0
9
Order By: Relevance
“…The positive effect of the Bactozyme additive on NDF digestibility in this study might be related to stimulation of growth of cellulolytic bacteria. However, the effects of DFM on DMI appeared varying in this study probably due to variation in products, methods of applying, roughage: concentrate ratio (Yang et al, 2000;Bowman et al, 2002).…”
Section: Discussionmentioning
confidence: 61%
“…The positive effect of the Bactozyme additive on NDF digestibility in this study might be related to stimulation of growth of cellulolytic bacteria. However, the effects of DFM on DMI appeared varying in this study probably due to variation in products, methods of applying, roughage: concentrate ratio (Yang et al, 2000;Bowman et al, 2002).…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, several researchers recorded an increase in DMI of dairy cows when fibrolytic enzymes was applied to forage before mixing with other ingredients (Lewis et al, 1999) or applied to TMR or concentrate portion of the diet (Bowman et al, 2002;Ware & Zinn, 2005). However, the effects of fibrolytic enzymes on DMI appear to be vary among enzymes products and the method of applying of enzymes (Bowman et al, 2002) A number of studies have examined the effects of fibrolytic exogenous enzymes on digestibility and milk production in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several researchers recorded an increase in DMI of dairy cows when fibrolytic enzymes was applied to forage before mixing with other ingredients (Lewis et al, 1999) or applied to TMR or concentrate portion of the diet (Bowman et al, 2002;Ware & Zinn, 2005). However, the effects of fibrolytic enzymes on DMI appear to be vary among enzymes products and the method of applying of enzymes (Bowman et al, 2002) A number of studies have examined the effects of fibrolytic exogenous enzymes on digestibility and milk production in dairy cows. In some studies, dietary addition of fibrolytic enzymes either to forages or concentrate portion increased milk production from 5-16% (Lewis et al, 1999;Gado et al, 2009;Holtshausen et al, 2011) as noticed at the current study but no milk response was reported in others (Elwakeel et al, 2007;Bernard et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme product was added to the entire concentrate according to the conclusions of Bowman et al (2002). The liquid enzyme preparation was sprayed (0.47 ml/kg of concentrate) onto the previously manufactured and cooled concentrate pellets in a horizontal mixer.…”
Section: Methodsmentioning
confidence: 99%
“…Beauchemin et al (2003) reviewed the use of enzymes in ruminants indicating an increase in DM and fibre digestion in vitro, in situ or in vivo and an increase in milk yield and weight gain in cattle, although results did not agree in all cases. Much of the variability can be attributed to factors such as type, dose and activity of the enzyme; application method and portion of the diet (forage or concentrate) to which the enzyme was applied and differences in the physiological status of the test animals (Bowman et al, 2002;Beauchemin et al, 2003). Addition of enzymes in the concentrate portion of the diet is especially interesting in practice when enzyme activity is not compromised (Bowman et al, 2002 and.…”
Section: Introductionmentioning
confidence: 99%